Fen bilimleri ve matematik dersi öğretim programlarının disiplinlerarası öğretim bağlamında incelenmesi: Fen bilimleri-matematik entegrasyonu. - ÜREDİ, Pelin; ÖZBİLEN, Ayşe Gül; ÜREDİ, Lütfi (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
In this research the overlap of the achievements in the secondary school science and mathematics curriculum in the context of interdisciplinary teaching was examined. The document rwviex method, one of the qualitative research designs, was used in the research. In order to ensure the reliability and data diversity of the data obtained, the interview tchnique was also used. 6 science teachers, 5 mathematics teachers an done field expert working in secondary schools in the central districts of Adana province participated in the research. The data obtained through semi-structured interview forms created as a result of the opinions of field experts and literature review were converted into written documents and content analysis was carried out. The findings resulting from the content analysiz were combined and interpreted with the findings of the document analysis made by field experts. Thus, incompatibilities regarding the overlap and functioning of the two curriculums were idetified.